Prevalence and characteristics of ventricular septal defects in a non‐racehorse equine population (2008‐2019) - Lisa De Lange (Wiley, 2021)
Abstract Background Ventricular septal defects (VSDs) are the most common congenital cardiac defect in horses. Objectives To identify prevalence, age, breed, and sex distribution of VSD and to describe associated clinical and ultrasonographic findings. Animals Hospital‐based population of 21 136 horses presented to the equine internal medicine department. Methods Medical records over a 12‐year period were reviewed for VSD confirmed by ultrasonography. Age, breed, sex, sport discipline, murmur, clinical signs, outcome, VSD type, VSD size, shunt velocity, cardiac dimensions, concomitant cardiac anomalies, and valvular regurgitations were recorded. Results From 1894 horses that underwent echocardiography, 54 had a VSD: 42 as an isolated lesion and 12 as part of complex congenital heart disease (CHD). Median age was 5 years (range, 0‐26) and 1 year (range, 0‐8), respectively. Warmbloods and males were overrepresented. In the isolated VSD group, only 15% had associated clinical signs and most horses had a perimembranous VSD (pmVSD; 36/42). Horses with a pmVSD and clinical signs showed a significantly lower maximal shunt velocity (3.77 vs 5.20 m/s; P < .001), higher VSD/Aortic root (Ao) diameter (0.52 vs 0.38; P = .05), higher left atrium/Ao diameter (1.94 vs 1.22; P < .001), and higher pulmonary artery/Ao diameter (1.15 vs 0.88; P = .005) compared to horses without clinical signs. All horses with complex CHD had clinical signs and abnormal cardiac dimensions. Conclusion and Clinical Importance Most isolated VSD were diagnosed only at a later age and were not associated with clinical signs. Horses with complex CHD were more likely to have or develop clinical signs at younger age.